The Role of the Constitutional Court in the Implementation of the Principle of Checks and Balances System - Вдовічен, Віталій (Revista San Gregorio. Universidad San Gregorio de Portoviejo,, 2020)
The article deals with the analysis of the place and role of the Constitutional Court in the system of separation of powers, for the effective implementation of the system of checks and balances. The institutional and legal model of interaction of constitutional justice authorities with legislative and executive bodies is formulated on the basis of the comparative legal analysis of the regulatory legal acts establishing the powers of constitutional jurisdiction authorities in the mechanism of implementation of the system of checks and balances on the example of different countries with different forms of government, a number of conclusions and suggestions are provided. On the basis of the conducted sociological survey, the author comes to the conclusion about the special level of efficiency of separate powers of constitutional justice authorities. This includes the possibility of applying the procedure for resolving conflicts between public authorities, which prescribes that in case of doubt about the powers of a state authority regarding the rights and obligations granted to it by the Constitution, the latter has the right to appeal to a constitutional jurisdiction authority; consideration by the constitutional justice authority of cases arising as a result of parliamentary, presidential elections or referendum; making a decision by the constitutional jurisdiction authority on bringing the President, ministers and other state officials to justice for violating the constitution; a mandatory interpretation of the law in order to resolve inconsistencies in the field of political powers.
Keywords: Constitutional Doctrine; Constitutional Justice; System of Checks and Balances; The Principle of Separation of Powers; The Constitutional Court